Exploring preference heterogeneity and willingness to pay for tourist facility attributes in Kenyir Lake, Malaysia - Wan Mohamad, Wan Norhidayah; Mzek, Tareq; Samdin, Zaiton; Hasan-Basri, Bakti (Malaysian Economic Association, 2022)
Natural environments with great recreational value can potentially support tourism, conserve natural areas and prevent environmental damage. However, visiting recreational destinations depends on several motivations related to visitors’ preferences. Therefore, this study aims to identify the heterogeneity of Kenyir Lake, Malaysia, visitors’ preferences and their willingness to pay (WTP) for tourist facility attributes. The choice experiment method has been widely used for economic valuation, and the latent class model can capture the heterogeneity of preferences by characterising respondents in various groups of preferences. The outcome of this study revealed heterogeneous preferences in two classes. The first class represented 91.3% and the second class represented 8.7% of respondents. Moreover, this study’s respondents showed positive WTP values for most attributes. However, the most preferred attribute was superior toilet service, with a WTP estimation of RM7.63 in Class 1. While in Class 2, the most preferred attribute was new jetty construction with a WTP estimation of RM1.99. The findings of this study can assist policymakers in implementing more effective policies as it has provided detailed information about visitors’ preferences for tourist facility attributes in Malaysia.